Bio-based succinic acid sample preparation and derivatization procedure optimisation for gas chromatography-mass spectrometry analysis - Jarukas, Laurynas; Kamarauskaitė, Justina; Marksa, Mindaugas; Trumbeckaitė, Sonata; Banienė, Rasa; Ivanauskas, Liudas (ScienceRise: Pharmaceutical Science, 2018)
This study focused on bio-based succinic acid sample preparation and derivatization conditions optimization using GC-MS analytical method. Succinic acid, the precursor of a wide range bio-compounds, especially it is important in accumulation of mitochondrial metabolite succinate (citric acid cycle) and during ischemia controls reperfusion injury through mitochondrial reactive oxygen production. Accurate determination of analytes is the key in metabolomics to use as low molecular biomarkers in case to improve diagnostic methods. Methods. Gas chromatography-mass spectrometry (GC-MS) method. For the quantitative determination of the succinic acid applied derivatization process by silylation using -bis- (trimethylsilyl) -trifluoroacetamide (BSTFA). Results. The derivatization agent BSTFA, the derivatization time of 3-4 hours and derivatization temperature at 70 °C were selected as the optimal derivatization condition for quantification of succinic acid by GС/MS in biological samples. The results show that GC-MS SIM method with evaporation was the most effective to quantify succinate in biological samples after ischemia/reperfusion injury. Selected ion monitoring (SIM) allowed to monitor a subset of fragments with their related mass values in a certain retention time (RT) range for a set of targets. Conclusions. DC – MS has several advantages for measurements of succinate concentration in small kidney tissue samples (lyophilized mitochondria). The method can be applied in small pieces of tissue - biopy samples, tissues from various organs